The effectiveness numeracy learning strategies for early grade students in elementary school: a systematic review - Mustika, Aisyah Senja; Riyadi, Riyadi; Kurniawan, Sandra Bayu (Universitas Ahmad Dahlan, 2025)
The implementation of the Independent Curriculum in 2022 places improving numeracy skills as one of the priority programs for basic education in Indonesia. Early numeracy skills are an important foundation for children's cognitive development and long-term academic success. This study aims to evaluate and identify the most effective early numeracy learning strategies in supporting the strengthening of elementary school students' numeracy skills. The research method used is a systematic literature review with a qualitative-descriptive approach. Data sources were obtained through manual searches of 18 scientific journal articles and 4 conference proceedings published in the last five years. Of the total 22 publications analyzed, six learning strategies were found to be consistently reported as effective: (1) explicit learning through short-term interventions, (2) the use of concrete manipulatives, (3) the use of visual representations, (4) providing corrective feedback, (5) involving parents in the learning process, and (6) game-based learning. The last strategy is the most dominant, mentioned in eight different studies, with variations of digital and traditional games adapted to the local context. The results of this study provide a comprehensive illustration of relevant and implementable approaches in early numeracy learning. These findings contribute to providing an empirical basis for policy makers and educators to design contextual, adaptive, and evidence-based numeracy learning programs.